Analisis Kesulitan Belajar IPA Siswa Kelas 6 di SDN 170 Pekanbaru - -, Eka Nurafni Sihotang; Mustika, Dea (Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
This research was motivated by the importance of understanding Natural Science (IPA) at the elementary school level and the indication of learning difficulties in grade 6 students of SDN 170 Pekanbaru. The purpose of this research is to analyze the factors that cause science learning difficulties in grade 6 students at the school. The research method used was descriptive qualitative with data collection through observation, interviews with students and teachers, and documentation. The results of the study show that there are two main factors causing science learning difficulties, namely internal and external factors. Internal factors include students' difficulty in understanding abstract science material, low motivation to learn, and lack of concentration during learning. Meanwhile, external factors that contribute to science learning difficulties are the lack of attention and support from parents at home, the influence of a play environment that is less supportive of learning, and the variety of teacher teaching methods that need to be improved. Thus, this study identifies the need for comprehensive interventions to overcome students' science learning difficulties, involving both internal aspects of students and external factors that influence them.